Illicit and unnatural practices : the law, sex and society in scotland since 1900 - Davidson, Roger, 1942- (Edinburgh University Press, 2018)
Using a wide range of prosecution and trial records, along with more recent newspaper coverage of court proceedings, this book furnishes a fascinating insight into the relationship between the law, sex, and society in modern Scotland.